The message of Luke the Saviour of the world - Wilcock, Michael (Leicester, UK IVP, 1979)
Includes bibliographical references.
"The Bible speaks today series has been placed in the library in memory of Gordon W. Craig, 1926-1990". Originally published under the title "The Saviour of the world".
Keywords: Bible. N.T. Luke -- commentaries